Conditions and factors affecting the accuracy of olfactometric detection - Petra Riedlova; Spiros Tavandzis; Josef Kana; Jaromir Roubec (Heliyon)
Introduction: The use of signal dogs for cancer detection is not yet routinely performed,but dogs and their powerful olfactory system have proven to be a unique and valuable tool for many lineages and are beginning to be incorporated into medical practice. This method has great advantages; the dog can detect a tumour in the human body already in preclinical stages, when the patient has no symptoms yet. The identification of cancer biomarkers to enable early diagnosis is a need for many types of cancer, whose prognosis is strongly dependent on the stage of the disease. However, this method also has its various pitfalls that must be taken into account. Aim: The aim of the study was to identify and highlight the factors that affect the level of detection accuracy, but also the conditions associated with olfactometric diagnosis. Methods: The study included 48 dogs and 48 handlers, that were part of the training between 2016 and 2023.All those who started olfactometry training and remained in training for at least one year were included in the study. The dogs ranged in age from 8 months to 12 years and were of different races and sexes. After long-term observation, a qualitative analysis was performed and factors that may play a role in the early detection of the disease were listed. Results: The results of the search for the different factors have been compiled into two groups, focussing on the actual handling of the patient biological sample from collection, processing, storage until transport, preparation of the sample,and detection. Focus on the actual work and behaviour of the dog and handler. Conclusion: There are many factors; however, it is worth addressing them because the canine sense of smell is one of the possible uses as a diagnostic method.